Can insider power affect employment? - Pilar Díaz-Vázquez; Dennis J. Snower (Institute for the Study of Labor (IZA), 2002)
Do firms reduce employment when their insiders (established, incumbent employees) claim higher wages? The conventional answer in the theoretical literature is that insider power has no influence on employment, provided that the newly hired employees (entrants) receive their reservation wages. The reason given is that an increase in insider wages gives rise to a counterveiling fall in reservation wages, leaving the present value of wage costs unchanged. Our analysis contradicts this conventional answer. We show that, in the context of a stochastic model of the labor market, an increase in insider wages promotes firming in recessions, while leaving hiring in booms unchanged. Thereby insider power reduces average employment.
Keywords: J42; J64; E24; J23; J31; 330; employment; labor demand; wage differentials; insider power; Lohnstruktur; Insider-Outsider-Modell; Arbeitsuche; Anspruchslohn; Marktmacht; Theorie